Trends in technical-vocational and secondary education in Latin America. - Corvalan-Vasquex, Oscar (1989)
Reviews the introduction of technical-vocational education as part of secondary education and as a leader to future education. This reform reassessed the orientation of the middle level education with a view to establishing a stronger link between education and employment.